Impact of mental health problems and social support on sleep quality: Follow-up before and during the first eight months of the COVID-19 pandemic in Chilean university students - Antúnez, Zaira; Vergara, Rodrigo C.; Langer, Álvaro I.; Santander, Jorge; Baader, Tomas; Álamo, Catalina; Arce, Mónica; Delgado, Bárbara; Laurin, Karen; Moncada, Catalina (Anales de Psicología / Annals of Psychology, 2023)
Introduction: Research has revealed high rates of mental health problems in university students before and during the COVID-19 pandemic, with effects on poor sleep quality; however, perceived social support appears to act as a protective factor. Objective: To assess the impact of mental health (anxiety, depression, and stress) on sleep quality, cross-sectionally and longitudinally, before and during the COVID-19 pandemic in Chilean university students, verifying whether perceived social support could act as a moderator in this relationship. Material and Methods: 1.619 university students in 2019 and 1.862 in 2020 answered questionnaires aimed at measuring depression, anxiety, stress, sleep quality, and perceived social support. Longitudinal analysis was performed with a fraction of the sample that responded in both years (n = 325). The scores of the instruments for both years were contrasted using a transition matrix and a multiple regression model. Results: High prevalence rates of mental health problems were found, with moderate and severe symptoms increasing in 2020. Sleep problems and the perception of low social support worsened. All mental health variables were found to predict sleep quality except for social support; longitudinally, the severity of poor sleep quality and depression increased. No significant moderation effects were found between perceived social support and the rest of the variables. Conclusions: The effect of the pandemic on mental health is complex, requiring concrete actions to provide students with psychological support.